Atmospheric Hg Levels in Tree Barks Due to Artisanal Small-Scale Gold Mining Activity in Bunut Seberang Village in Indonesia - Azhary Taufiq; Melya Riniarti; Endang Linirin Widiastuti; Hendra Prasetia; Slamet Budi Yuwono; Ceng Asmarahman; Tedy Rendra (Atmosphere, 2022)
Mercury (Hg) is a useful heavy metal; however, it is toxic to both humans and the environment. Tree bark is an excellent bioindicator, which has been proven to be effective in studying the level of atmospheric Hg contamination. This study aimed to determine the distribution of evaporated Hg using the total weight of Hg (THg) in tree barks in Indonesia at the artisanal and small-scale gold mining (ASGM) area of Bunut Seberang Village and Lampung University, respectively. Samples were taken using purposive sampling, based on the criteria of forestry trees at a height level of 1.3 m above ground as wide as 100 cm2. The samples were analyzed by atomic absorption spectrometry and Scanning electron microscopy to determine the levels of THg and to investigate the bark structures. Results showed that the highest THg values were found in a Magnolia champaca sample (56.5 µg), followed by Swietenia mahagoni (45.8 µg) and Swietenia mahagoni (33.5 µg). All species studied showed THg levels in the tree barks at an elevation from 30 to 320 m above sea level. The Hg amounts found in the sampled barks indicated the dispersion of Hg throughout the ASGM area, which signified hazardous atmospheric conditions in the area.